Ежегодник Комиссии Международного Права 2017 Том II Часть первая - United Nations International Law Commission (United Nations, 2025)
The International Law Commission was established in 1947 with a view to carrying out the responsibility of the General Assembly, under article 13(1)(a) of the Charter of the United Nations, to “initiate studies and make recommendations for the purpose of ... encouraging the progressive development of international law and its codification.” Since its first session in 1949, the Commission has considered a wide-range of topics of international law and made a number of proposals for its codification and progressive development, some of which have served as the basis for the subsequent adoption of major multilateral treaties. The Yearbook of the International Law Commission contains the official records of the Commission and is an indispensable tool for the preservation of the legislative history of the documents emanating from the Commission, as well as for the teaching, study, dissemination and wider appreciation of the efforts undertaken by the Commission in the progressive development of international law and its codification. Volume II (Part One) reproduces the edited versions of the official documents considered by the Commission at the respective annual session.